Organizational commitment among construction professionals - Nur Syamimi, Baharudin; Mohyin, Nur Affah (2013)
Construction activities are recognized as complex and typically involve various parties. Each party has own responsibilities which would contribute to a success of a construction project. Therefore, commitment of all parties is essential. Generally, commitment in the workplace influences organizational effectiveness and employee behaviour. Thus, commitment has been viewed as a significant power in ensuring the success of the project as well as to the organization’s profitability. Besides, project outcomes and working performance can be affected by employees’ commitment. For that reason, it is crucial to do this study on commitment particularly amongst construction professionals. The aim of this paper is to review various factors influencing the organizational commitment and the consequences of commitment. The review of the literature shows that the actors of commitment amongst construction professionals can be categorized into four main categories which are individual characteristics, organizational characteristics, job characteristics and experience of the workplace. The main consequences of commitment are productivity, satisfaction, readiness to change and intention to stay. The gaps identified by this literature synthesis are the origin of important questions for future research.